140k views
17 votes
Solve for s.

3(s+8)=36


s = 2

s = 4

s = 8

s = 12

User Kingrolo
by
5.0k points

2 Answers

1 vote

Answer:

s = 4

Explanation:

To solve for "s", we need to simplify the distributive property on the LHS.


\rightarrow 3(s + 8) = 36


\rightarrow 3s + 24 = 36

Now, let's solve for "s".


\rightarrow 3s + 24 = 36


\rightarrow3s + 24 - 24 = 36 - 24


\rightarrow3s = 12


\rightarrow \boxed{s = (12)/(3) = 4}

User TheRyanMark
by
5.7k points
8 votes

Answer:

3(s+8) = 36

= 3(4+8) = 36

=3(12) = 36

= 3×12 = 36

User Nidhin Rejoice
by
5.2k points